ANALISIS DATA MINING HOTEL BOOKING MENGGUNAKAN MODEL ID3 - Agus Budiyantara; Andreanus Kevin Wijaya; Anthony Gunawan; Michael Rolland (Universitas Bunda Mulia, 2021)
The rapid development of information technology in this era makes it easier for someone to get information. Many business sectors are now promoting their products or services on the internet. An example is a hotel, in the technological era now we can easily find out about hotel information, ranging from location, price, and others. With the convenience to get information about this hotel, customers are indirectly increasing in a hotel. This of course causes the data contained in a hotel to increase as well. These data can be processed until we get an output and there is also data that is missing or cannot be processed. The data that can be processed can be analyzed until finally it becomes an information and prediction. In this journal, we will explain the Data Mining analysis in a hotel to analyze the success rate of a hotel. By doing this analysis, you will get insights about the level of success of the hotel and can also predict the future. Thus later the results of this analysis can be used by the hotel to assist in better decision making. Processing data in this study using the Rapid Miner application by entering data of customers who make hotel reservations